2011
DOI: 10.1159/000329602
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase II Study of Drug-Eluting Beads versus Transarterial Chemoembolization for Unresectable Hepatocellular Carcinoma

Abstract: Background: Transcatheter arterial chemoembolization (TACE) is the standard treatment in selected patients with unresectable hepatocellular carcinoma (HCC). Drug-eluting particles are developed to reduce side effects and improve efficacy. We present safety data of a prospective randomized phase II study with doxorubicin-eluting superabsorbent polymer (SAP) microspheres. Material and Methods: We prospectively included 30 HCC patients with different Barcelona Clinic Liver Cancer (BCLC) stages (A = 3, B = 19, C =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 37 publications
3
92
1
Order By: Relevance
“…None of those trials demonstrated a difference in survival, but patients treated with drug-eluting bead tace consistently experienced fewer adverse events [69][70][71][72] .…”
Section: Summary Of Evidencementioning
confidence: 99%
“…None of those trials demonstrated a difference in survival, but patients treated with drug-eluting bead tace consistently experienced fewer adverse events [69][70][71][72] .…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Complications mainly include pleural effusion, gastric ulcers, esophageal variceal bleeding, liver failure, cholangitis, and abscess formation (22,23). Aminotransferase levels also rise but they are generally believed to return to normal after a few days.…”
Section: Complications Of Drug-loaded Microspheresmentioning
confidence: 99%
“…Surprisingly often, however, this crucial information on the formulation is not fully described and summarized in clinical reports [12,53,[83][84][85][86]. When it is reported, ratios of aqueous:LIP appear to be in the range of 4:1 to 1:3.33, but are mostly 1:1 [87][88][89][90][91][92]. As suggested by the in vitro data (Figure 4), only aqueous:LIP ratios of 1:2-4 will result in w/o emulsions with sustained in vitro release of DOX.…”
Section: In Vivo Behavior Of Lipdox In the Hepatobiliary Systemmentioning
confidence: 99%